THE EFFECT OF PLANT THERAPY ON THE LEVEL OF LONELY ELDERLY AT THE WREDA HOUSE - Maya Cobalt Angio Septianingtyas; Vivi Sovianti; Arni Nur Rahmawati (Indonesian Journal of Community Health Nursing, 2023)
ABSTRACT Introduction: The elderly experience changes in physical, biological and psychological functions. This decreased function affects mobility and relationships with other people so that the elderly often experience loneliness, or alone. Efforts to overcome the problem of loneliness in the elderly require planting therapy with an emotional and psychological approach. The purpose of this study was to determine whether there was an effect of planting therapy on the loneliness level of the elderly at the "Pucang Gading" Elderly Social Service Home. Research Methods: The method and design of this study used quantitative research with a quasi-experimental design and the type of research design used was one group pre-post test with 32 respondents. The sampling technique used purposive sampling. The measuring tool used is the UCLA Loneliness Scale Version 3 in Javanese. Wilxocon rank test statistical test with a significant level of p-value <0.05. Results: Research resultsshowed the effect of planting therapy on the loneliness level of the elderly with a p-value <0.000. Conclusion: The conclusion of the study is that there is an effect of plant therapy on the loneliness level of the elderly at the Pucang Gading Elderly Social Service Home. For future research, it is hoped that this can become a reference material or library material related to planting therapy to overcome the level of loneliness in the elderly and future researchers can anticipate the weaknesses in this study, and are expected to be able to develop research by conducting planting therapy using other methods such as planting plants with hydroponics which simpler by utilizing existing land. Keywords :Planting therapy, level of loneliness, elderly